Are early childhood teachers ready for digital transformation of instruction in Mainland China? A systematic literature review. (January 2021) - Luo, Wenwei; Berson, Ilene R.; Berson, Michael J.; Li, Hui
Highlights: Technologies have an increasing role in Chinese early childhood teachers' instructional practices. The social environment has influenced teachers' technology utilization practices. Most teachers had strong positive attitudes towards technology but limited experience with digital technology use. The influence of theoretical constructs in framing research questions and findings is ongoing but needs more exploration. The progress, problems, and prospect of digitalizing early childhood are discussed. Abstract: This review aims to synthesize existing studies to understand whether Chinese early childhood teachers are ready for digital transformation of their instruction and to describe research trends that define the current state of technology integration in early childhood settings throughout China. The literature was systematically searched using English and Chinese electronic databases, and 46 articles published between 2012 and early 2020 were sampled and analyzed. An integrated approach guided the interpretation of the sampled articles with a focus on sociocultural support for the digitalization of early childhood in Mainland China, Chinese teachers' attitudes and competencies for integrating technology into their instructional practices, and the influence of theoretical constructs in framing research questions and findings. The progress, problems, and prospect of digitalizing early childhood are discussed. The findings suggest that Chinese early childhood teachers are not quite ready for optimizing the integration of digital tools into their classrooms, and teacher education may play a critical role in fostering technological competencies and confidence of the next generation of early childhood educators.